THE NANOSTRUCTURED MULTIPURPOSE BIOPOLYMERS AND NANOBIOCOMPOSITES ON THEIR BASIS FOR DIAGNOSTICS AND THERAPY - B. G. Sukhov (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
A novel original approach to self-organization of hybrid nanobiostructures possessing unique complex of physicochemical and biological properties (extremely demanded for noninvasive diagnosis and. therapy) is discussed.